2021
DOI: 10.1113/jp282321
|View full text |Cite
|
Sign up to set email alerts
|

Corticothalamic projections deliver enhanced responses to medial geniculate body as a function of the temporal reliability of the stimulus

Abstract: Ageing and challenging signal‐in‐noise conditions are known to engage the use of cortical resources to help maintain speech understanding. Extensive corticothalamic projections are thought to provide attentional, mnemonic and cognitive‐related inputs in support of sensory inferior colliculus (IC) inputs to the medial geniculate body (MGB). Here we show that a decrease in modulation depth, a temporally less distinct periodic acoustic signal, leads to a jittered ascending temporal code, changing MGB unit respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 119 publications
(286 reference statements)
3
7
0
Order By: Relevance
“…3J ), indicating that A1 feedback modulation may enhance the synchronized responses of MGB neurons to amplitude-modulated sounds. This is consistent with recently published work ( Kommajosyula et al. 2021 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…3J ), indicating that A1 feedback modulation may enhance the synchronized responses of MGB neurons to amplitude-modulated sounds. This is consistent with recently published work ( Kommajosyula et al. 2021 ).…”
Section: Resultssupporting
confidence: 94%
“…More specifically, we found corticothalamic modulations decreased spontaneous background activity and increased stimulus-driven response, resulting in increased SNR of MGB neurons during sensory processing. Moreover, A1 feedback modulation enhanced stimulus-synchronized responses of MGB neurons, consistent with recent awake research ( Kommajosyula et al. 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…Repetition enhancement has also been observed in the MGB in response to temporally degraded stimuli that are hypothesized to engage top-down resources to compensate for bottom-up acoustic information loss ( Cai et al, 2016 ; Kommajosyula et al, 2019 ). Interestingly, this enhancement is reversed when cortico-thalamic pathways are blocked, further suggesting that repetition enhancement in the auditory system reflects a top-down phenomenon ( Kommajosyula et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, repetition enhancement was observed in all three areas. Lesicko et al 2022 and Kommajosyula et al 2021 also found repetition enhancement in the IC and auditory thalamus of awake rodents, respectively. This is consistent with our findings that repetitive stimuli evoked facilitation, and periodic target speaker sequences evoked stronger responses than random target speaker sequences (Figure 5C).…”
Section: Discussionmentioning
confidence: 83%
“…Instead, our findings suggest that PE (i.e., repetition adaptation) and P (i.e., repetition facilitation) neurons coexist in the auditory cortex. The observation of auditory cortex inactivation reduces or blocks the repetition enhancement in the auditory midbrain and thalamus indicates prediction signals originate from P neurons in the auditory cortex (Lesicko et al, 2022; Kommajosyula et al, 2021).…”
Section: Discussionmentioning
confidence: 99%